Numerical analysis to study the tensile behaviour of a spring-steel-wire-reinforced aluminium alloy metal matrix composite. (September 2015) - Merzkirch, Matthias; Meissner, Marius; Schulze, Volker; Weidenmann, Kay André
The reinforcement of composite extruded light metal profiles offers a high potential in terms of weight reduction and the improvement of mechanical properties, both of which are essential for components in lightweight space frame constructions. In a previous study, the mechanical properties under tensile loading of spring-steel (301SS)-wire-reinforced aluminium extrusions based on EN AW-6082 were investigated in terms of a varying reinforcing ratio. The aim of the current study is to minimize the effort needed to gather mechanical data by calculation of the deformation and damage behaviour under tensile loading of 11.1 vol.% spring-steel-reinforced EN AW-6082. The simulation of the push-out test provided specific parameters concerning the interfacial properties – like the radial strength – needed for modelling the tensile test. It could be shown that the simulation of the tensile test is in good agreement with the experimental results, concerning quantitative values (stress–strain curve) and qualitative behaviour (necking and debonding).